2014
DOI: 10.2166/washdev.2014.147
|View full text |Cite
|
Sign up to set email alerts
|

Why are some latrines cleaner than others? Determining the factors of habitual cleaning behaviour and latrine cleanliness in rural Burundi

Abstract: Access to improved sanitation is fundamental for the prevention of diarrhoea and other diseases.However, for a sanitation facility to be safe, its cleanliness must be assured. The aim of the present study was, first, to assess how cleaning behaviour, household characteristics and infrastructural factors influenced latrine cleanliness and, second, to assess which psychological factors influenced cleaning behaviour. In a study in rural Burundi, 762 standardised household interviews with the primary household car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In this study, shared sanitation quality was measured as a total entity that included the roof, superstructure, as well as hygienic conditions. Most of these indicators were used by other studies [510, 52] that aimed at assessing the hygienic conditions of sanitation facilities. The advantage of using all these indicators as used in this study is that the measure of quality is all-inclusive, and not only focused on hygienic aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, shared sanitation quality was measured as a total entity that included the roof, superstructure, as well as hygienic conditions. Most of these indicators were used by other studies [510, 52] that aimed at assessing the hygienic conditions of sanitation facilities. The advantage of using all these indicators as used in this study is that the measure of quality is all-inclusive, and not only focused on hygienic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cleanliness and maintenance, studies have also highlighted the importance of aspects such as hygienic status of sanitation facilities, state of the superstructure, presence of smell, presence of flies, and the state of the slab (especially in the case of pit latrines) in defining the quality of shared sanitation [510]. What is evident from these studies is that quality of sanitation facilities is determined by maintenance practices such as cleaning or lack thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Household use of latrines and cleaning before or after use could result in cleaner latrines that smell less. Sonego and Mosler (2014) found habitual cleaning behaviour to be the strongest predictor of latrine cleanliness.…”
Section: Relating Status Of Pit Latrines To Their Performancementioning
confidence: 90%
“…Research has shown that the presence of a door, superstructure quality (in terms of height and construction materials for walls) as well as the slab type, affect the cleanliness of a latrine (Sonego & Mosler, 2014). Absence of a roof over the latrine and temporary superstructures as opposed to brick superstructures positively correlated with high numbers of flies (Irish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] It comprises a broad array of potential behavioral determinants derived from major theories of social and health psychology and provides a guideline for selecting behavior change interventions based on behavioral determinants identified in the target populations. The RANAS model has been successfully applied to predict and change the frequency of handwashing at key handwashing situations in several countries.…”
Section: Introductionmentioning
confidence: 99%